On Quina and demi-Quina scraper handling: Preliminary results from the late Lower Paleolithic site of Qesem Cave, Israel. (4th April 2016) - Zupancich, Andrea; Lemorini, Cristina; Gopher, Avi; Barkai, Ran
Abstract: Most of the studies related to the function of Paleolithic stone tools carried out so far focused mainly on the analysis of the worked materials and the activities performed. On the other hand, only few works included an analysis of the tool griping area/s, and the wear derived by object manipulation. Here we present the results of an experimental framework dedicated to the interpretation of the griping modes of two types of flint scrapers, Quina and demi-Quina scrapers, which represent a very meaningful component of the lithic assemblages unearthed at the late Lower Paleolithic site of Qesem Cave (Israel). Our study includes the analysis of both a selected sample of archeological scrapers and of experimental replicas. We were able to underline the efficiency of different types of prehension modes while isolating diagnostic wears related to each of the adopted solutions. The experiments allowed defining wears related to several handling solutions, creating a traces collection to be compared to the ones identified on the archeological sample. The results obtained so far suggest a preference towards a free hand manipulation of the scrapers, even though wear related to wrapping and also to a probable insertion of the objects in a haft have been identified as well. This work allows providing preliminary insights related to the handling solutions adopted by the human groups at Qesem Cave, underlining the overall high level of technological knowledge characterizing the Middle Pleistocene inhabitants of the site.